2021
DOI: 10.3892/ol.2021.13078
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA regulates the onset and progression of cancer through the mitogen‑activated protein kinase signaling pathway (Review)

Abstract: The rapid increase in cancer morbidity and mortality worldwide is a major challenge for public health providers. Therefore, there is an urgent need to explore the molecular mechanism of tumorigenesis and identify potential diagnostic biomarkers and therapeutic methods. Circular RNA (circRNA) is characterized by a stable structure and tissue-specific expression; these features are useful in medical research and clinical applications. In recent years, with the development of high-throughput sequencing technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…Post recurrence in TNBC patients, MAPK overexpression correlated with poor survival (Eralp et al 2008 ; Bartholomeusz et al 2012 ). Activating MAPK/JNK and p38MAPK pathway causes damage to mitochondria, which is connected with disease progression and prognosis of many cancers (Lai et al 2021 ). p38 MAPK regulates cell fate by mediating cell survival or death depending on the type of stimulus and the specific cell type.…”
Section: Signaling Pathways That Circrnas Use To Regulate Breast Canc...mentioning
confidence: 99%
“…Post recurrence in TNBC patients, MAPK overexpression correlated with poor survival (Eralp et al 2008 ; Bartholomeusz et al 2012 ). Activating MAPK/JNK and p38MAPK pathway causes damage to mitochondria, which is connected with disease progression and prognosis of many cancers (Lai et al 2021 ). p38 MAPK regulates cell fate by mediating cell survival or death depending on the type of stimulus and the specific cell type.…”
Section: Signaling Pathways That Circrnas Use To Regulate Breast Canc...mentioning
confidence: 99%
“…Colorectal cancer. Colorectal cancer (CRC) is the fourth most deadly cancer in the world, largely due to its non-specific symptoms and late-stage diagnosis, resulting in a 5-year relative survival rate of 14% (54). However, the 5-year survival rate for localized CRC is much higher at 90% (55,56).…”
Section: Circ_nrip1 In Malignant Tumorsmentioning
confidence: 99%
“…Because of the deficiency of 5′ and 3′ terminals in structures, circRNAs are more stable than linear RNAs ( Li et al, 2015 ). Studies have showed the important roles of aberrant circRNA-associated signaling in cancer pathogenesis and therapeutic response ( Lai et al, 2021 ; Chen et al, 2022 ). Because of their unique closed-loop form and structural stability, circRNAs have been serving as novel prognostic and therapeutic targets for human cancers ( Jiao et al, 2021 ; Lan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%